Aspecten : De computer in de visuele kunst - Cohen, Harold; Coqart, Roger; Franke, Herbert W.; Mallary, Robert; Marcus, Aaron (Brussel : ICSAC - Internationaal Centrum voor Structuuranalyse en Constructivisme, 1981)
Bangert, Colette & Charles ; Barbadillo, Manuel ; Basset, Klaus ; Belfort, Groupe ; Beyls, Peter ; Cohen, Harold ; Coqart, Roger ; Franke, Herbert W. ; Guest, Julius ; Hashimoto, Sozo ; Horvat, Miljenko ; Kolomyjec, William B. ; Leavitt, Ruth ; Mallary, Robert ; Marcus, Aaron ; Mohr, Manfred ; Molnar, Vera ; Palyka, Duane ; Schneeberger, Reiner ; Schwartz, Lillian ; Tyler, Christopher W. ; Zajec, Edvard ; Ziljak, Vilko
Biografie, Bibliografie
Nederlands & Engels & Frans & Duits
boek